Comparison between UroLift and Transurethral Resection of the Prostate in the Treatment of Benign Prostatic Hyperplasia - Khair, Sinan Diya; Ismail, Ali Abdul-Baqi (NIU Journal of Health Sciences, 2026)
Background: Benign Prostatic Hyperplasia (BPH) is among the most prevalent chronic urological conditions in aging men, producing lower urinary tract symptoms (LUTS) that markedly reduce quality of life. Transurethral Resection of the Prostate (TURP) has long served as the surgical gold standard, yet it carries substantial risks of bleeding, TUR syndrome, prolonged catheterization, and long-term sexual dysfunction. The Prostatic Urethral Lift (UroLift) is a minimally invasive, non-ablative alternative that mechanically retracts obstructing prostatic lobes using permanent implants. Problem: There is limited comparative, prospective evidence on the relative efficacy and safety of UroLift versus TURP under the specific clinical, economic, and cultural conditions of Iraq. Methods: A prospective comparative clinical study was conducted at The Nasiriyah Center for Urology and Nephrology from October 2022 to April 2023, enrolling 21 male BPH patients divided into a UroLift group (9 patients) and a TURP group (12 patients). Outcomes assessed at 3 months included IPSS, Quality of Life index, maximum urinary flow rate (Qmax), Post-Void Residual (PVR) volume, serum PSA, and surgical complications. Data were analyzed with SPSS v26 using t-tests, chi-square, and Fisher's Exact test (significance at p ≤ 0.05). Results: Both techniques produced significant symptomatic improvement, but UroLift was statistically superior in IPSS (3.44 ± 0.88 vs 5.08 ± 2.49; p = 0.0018), Qmax (21.33 ± 5.61 vs 16.17 ± 4.56 mL/s; p = 0.031), PVR (23.56 ± 23.77 vs 52.05 ± 32.11 mL; p = 0.038), and PSA (0.78 ± 0.61 vs 1.48 ± 0.95; p = 0.050). Overall complications were far lower with UroLift (33.33% vs 91.67%; p = 0.005), which uniquely preserved sexual function in 100% of patients. Conclusions: UroLift achieved efficacy comparable or superior to TURP in relieving obstruction while offering a substantially safer profile and complete preservation of sexual function, making it a compelling minimally invasive option for suitable BPH patients. Keywords: Benign Prostatic Hyperplasia; UroLift (Prostatic Urethral Lift); Transurethral Resection of the Prostate (TURP); Lower Urinary Tract Symptoms; Minimally Invasive Surgery.